An apply implementation of a carrier-based three-dimensional space vector PWM technique for three-phase four-leg voltage sag generator with microcontroller - Worrajak Muangjai (2018)
This paper presents an apply implementation of a carrier-based three-dimensional space vector PWM technique for three-phase four-leg voltage sag source generator with microcontroller (SagGen). The implementation of the 3-D SVPWM needs quite a bit of digital logic and computational power and it seems to be the easiest way to generated standard voltage sag base on IEC-61000 and SEMI F47 standard and it might be a software and hardware burden even for recent digital signal processor (DSP) systems. Therefore, this paper presents a simple three-phase four-leg with carrier-based three-dimensional space vector PWM technique. The proposed technique can be implemented with microcontroller. The performance of proposed PWM strategy has been investigated and verified through simulations and experimental results for three-phase four-leg voltage source generator. © 2013 American Scientific Publishers All rights reserved.